Formulation of Nanoemulsion Sunscreen of Centella asiatica (L.) Extract and Its Effectivity Test - Rini Dwiastuti; Valentina Putri Embun Kinanti; Maria Andriani Gelu; Agustina Setiawati; Lutfi Chabib (Sanata Dharma University, 2025)
Sunscreen protects against ultraviolet (UV) rays. It has a Sun Protection Factor (SPF) value. Centella asiatica (L.) is a herbal plant that contains flavonoid and triterpenoid compounds as antiphotoaging agents. Development of Centella asiatica (L.) extract in nanoemulsion preparation increases its solubility in water and absorption. This study aims to obtain the optimum formula of Centella asiatica (L.) nanoemulsion preparation from the combined use of Tween-80 and Propylen glycol surfactants and determine the effectiveness of Centella asiatica (L.) extract in vitro. The effectiveness of Centella asiatica (L.) extract was tested in vitro using UV-Vis spectrophotometry expressed by SPF value. Development of Centella asiatica (L.) extract nanoemulsion formula using a combination of surfactants Tween-80 and Propylen glycol with factorial design 2 factors and 2 levels. P-value0.05 stated that there is a statistically significant difference in the formula. Centella asiatica (L.) extract has protective power against UV rays at concentrations of 120, 240, and 360 xg with SPF-values of 8.999, 19.219, and 29.569, respectively. Meanwhile, the nanoemulsion response analysis revealed the response of the nanoemulsion produced (p0.05). The optimum formula obtained was found in the nanoemulsion formula with a combination of Tween-80 and PG at a low level.